Role of ABCB1 and glutathione S‑transferase gene variants in the association of porphyria cutanea tarda and human immunodeficiency virus infection - Pagnotta, Priscila Ayelén (2020)
In Argentina, porphyria cutanea tarda (PCT) is strongly associated with infection with human immunodefi-ciency virus (HIV); however, whether the onset of this disease is associated with HIV infection and/or the antiretroviral therapy has not been determined. The ABCB1 gene variants c.1236C>T, c.2677G>T/A and c.3435C>T affect drug efflux. The GSTT1 null, GSTM1 null and GSTP1 (c.313A>G) gene variants alter Glutathione S-transferase (GST) activity, modifying the levels of xenobiotics. The aim of the present study was to evaluate the role of genetic variants in initia-tion of PCT and to analyze the genetic basis of the PCT-HIV association. Control individuals, and HIV, PCT and PCT-HIV patients were recruited, PCR-restriction fragment length polymorphism was used to genotype the ABCB1 and GSTP1 variants, and multiplex PCR was used to study the GSTM1 and GSTT1 variants. The high frequency of c.3435C>T (PCT and PCT-HIV) and c.1236C>T (PCT) suggested that the onset of PCT were not specifically related to HIV infection or antiret-roviral therapy for these variants. c.2677G>T/A frequencies in the PCT-HIV patients were higher compared with the other groups, suggesting that a mechanism involving antiretroviral therapy served a role in this association. PCT-HIV patients also had a high frequency of GSTT1 null and low frequency for GSTM1 null variants; thus, the genetic basis for PCT onset may involve a combination between the absence of GSTT1 and the presence of GSTM1. In conclusion, genes encoding for proteins involved in the flow and metabolism of xenobiotics may influence the PCT-HIV association. The present study is the first to investigate the possible role of GST and ABCB1 gene variants in the triggering of PCT in HIV-infected indi-viduals, to the best of our knowledge, and may provide novel insights into the molecular basis of the association between PCT and HIV.